Should agricultural employment in transition economies be encouraged? - Zvi Lerman (IZA World of Labor, 2017)
The increase in agricultural employment in Central Asia and Trans-Caucasus over the last two decades has had a detrimental effect on agricultural labor productivity and rural family incomes. Transition countries in the former USSR cannot, however, encourage exits from agriculture (as, for instance, in east Germany or the Czech Republic) due to the risk of mass rural–urban migration, which may exacerbate growing urban unemployment. With large rural populations, state budgets would be unable to deal with a new wave of unemployed in urban areas.
Keywords: L26; 330; agricultural labor; self-employment in agriculture; rural entrepreneurship; individualization of agriculture